2019
DOI: 10.1242/jcs.230649
|View full text |Cite
|
Sign up to set email alerts
|

Reliable imaging of ATP in living budding and fission yeast

Abstract: Adenosine triphosphate (ATP) is a main metabolite essential for all living organisms. However, our understanding of ATP dynamics within a single living cell is very limited. Here, we optimized the ATP-biosensor QUEEN and monitored the dynamics of ATP with good spatial and temporal resolution in living yeasts. We found stable maintenance of ATP concentration in wild-type yeasts, regardless of carbon sources or cell cycle stages, suggesting that mechanism exists to maintain ATP at a specific concentration. We fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 43 publications
5
56
0
Order By: Relevance
“…We recently developed a reliable monitoring system for cytoplasmic ATP concentrations in living yeast cells using the ATP biosensor QUEEN (Takaine et al, 2019). We conducted a more detailed examination of ATP dynamics in wild-type and mutant yeast cells using this system in the present study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently developed a reliable monitoring system for cytoplasmic ATP concentrations in living yeast cells using the ATP biosensor QUEEN (Takaine et al, 2019). We conducted a more detailed examination of ATP dynamics in wild-type and mutant yeast cells using this system in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Adenosine triphosphate (ATP) is the main energy currency used by all living organisms. Due to high demand, the turnover rate of ATP is estimated to be less than one minute in yeast and metazoans (Mortensen, Thaning et al, 2011, Takaine, Ueno et al, 2019). In addition to its role as energy currency, recent studies reported that ATP may influence the balance between the soluble and aggregated states of proteins, suggesting that proteostasis is maintained by energy-dependent chaperones and also by the property of ATP as a hydrotrope to solubilize proteins (Hayes, Peuchen et al, 2018, Patel, Malinovska et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation that different levels of ATP may induce different cellular behaviours comes as increasing cell heterogeneity in ATP levels is being experimentally characterised. Intracellular ATP has been quantified to vary between 0.32-2.76mM in a bacterial population 39 , 3.7-3.9mM in HeLa cells 41 , 3-4mM in living yeast cells 40 and over a several-fold change occurs in different tissues of a plant 42 . The connection between energy variability and cellular decision-making has also been discussed 9/25 previously 30,54 , further supporting the hypothesis that energy diversity may modulate the number of regulatory states supported by a cell, playing an important causal role in inducing variability in cellular decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…However, continuous measurements of ATP, and hence glycolytic startup dynamics, have not been studied at a single-cell level. In recent years several fluorescence-based biosensors for in vivo monitoring of ATP in single cells have been developed, including the AT1.03 and the QUEEN sensor 23,24 . However, these sensors use fluorescent proteins (FPs) that are pH-sensitive in the physiological range where the intracellular pH of budding yeast operates 17,[25][26][27][28][29] .…”
Section: Introductionmentioning
confidence: 99%